FAKTOR – FAKTOR MENDASAR KEJAHATAN SIBER TERHADAP KEMANUSIAAN : Key Determinants Of Cybercrimes Targeting The Human Population - Tri Ginanjar Laksana; Sri Mulyani (Faculty of Law, Trisakti University, 2023)
The issue of cyber crimes against humanity is rapidly emerging as a worldwide concern in the present day. Cybercrime, including activities like identity theft, online fraud, and cyberattacks, has a detrimental influence on society and people. This study examines the factors that lead to cyber crimes targeting the human population. We must be comprehensively aware of these constituent factors to enhance our efforts in combating cybercrime and safeguarding our digital security. In order to address this research question, we used normative juridical and empirical juridical research methodologies. We conducted a descriptive analysis and utilized both primary and secondary data sources. The study findings indicate the imperative need to address and counteract cybercrime against humanity. Collaboration among individuals, organizations, and governments is necessary to implement suitable security measures effectively and enhance public knowledge of cybercrime. In order to safeguard humanitarian interests, we must persist in examining and comprehending the fundamental elements of cybercrime. Through persistent endeavors and robust collaboration, we can enhance the security of the digital realm and safeguard society from cybercriminal activities.